2011
DOI: 10.1620/tjem.225.13
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cerebral Circulation in Patients with Slow Coronary Flow

Abstract: Slow coronary flow (SCF) is characterized by delayed opacification of coronary arteries during coronary angiography and is associated with myocardial perfusion abnormalities, ischemia or myocardial infarction. We hypothesized that SCF could be a part of systemic circulatory abnormalities. Therefore, the present study was conducted to investigate whether cerebral blood flow velocity is altered in patients with SCF. The study included 16 patients suffering from chest pain with angiographically proven SCF and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…In previous studies, it was also found that there might be concomitant slow flow in the cerebral circulation in patients with CSF. This suggests that slow flow is not a specific disease to myocardium, and it is also a systemic disease (21). In our study, CRP was found not to be associated with mean TFC and salusin-β.…”
Section: Discussioncontrasting
confidence: 64%
“…In previous studies, it was also found that there might be concomitant slow flow in the cerebral circulation in patients with CSF. This suggests that slow flow is not a specific disease to myocardium, and it is also a systemic disease (21). In our study, CRP was found not to be associated with mean TFC and salusin-β.…”
Section: Discussioncontrasting
confidence: 64%
“…Patients with CSF often present with recurrent unstable angina pectoris, arrhythmias, and cardiovascular and cerebrovascular events, and they generally have a poor prognosis ( 6 , 34 ). Therefore, early identification of patients with high risk of CSF is crucial for defining preventive treatment strategies and improving the quality of life and survival prognosis for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiovascular and cerebrovascular patients, decreased endothelium-dependent vasodilation due to a reduction in nitric oxide release in the microvascular arteries is a risk factor [ 14 ]. Karakaya et al observed that the velocity of cerebral blood flow was greatly reduced in individuals with CSF [ 15 ]. Endothelial irregularity appears to be a systemic condition that affects both the coronary and peripheral arteries.…”
Section: Discussionmentioning
confidence: 99%